Management of bleeding events and invasive procedures in patients with haemophilia A without inhibitors treated with emicizumab - Pierre Fontana; Lorenzo Alberio; Manuela Albisetti; Anne Angelillo-Scherrer; Lars M. Asmis; Alessandro Casini; Bernhard Gerber; Lukas Graf; Inga Hegemann; Wolfgang Korte; Maria Martinez; Jan-Dirk Studt; et al. (Swiss Medical Weekly, 2020)
INTRODUCTION